Cultural Hybridity and Postmodernism: Vietnam and the West - Luong, Hy Van (VNU Journal of Science: Social Sciences and Humanities; Vol 32 No 1S, 2016)
Postmodernism in Western humanities and social sciences emphasizes multivocality and cultural hybridity in the so-called postmodern era. On the basis of data on urban wedding ceremonies and rural spiritual space from northern and southern Vietnam, this paper suggests: Multivocality and cultural hybridity have long existed in Vietnam; 2. The theoretical linkage of multivocality and cultural hybridity to the postmodern era is rooted in the West’s particular historical and cultural trajectories. Such a linkage does not work well in many non-Western contexts, including Vietnam.